IBM eserver zSeries 990 technical introduction - Ogden, Bill (IBM redbooks., 2003)
The IBM eServer zSeries 990 provides major extensions to existing zSeries architecture and capabilities. The concept of books and channel subsystems are added to the architecture, and the maximum number of LPARs is increased. These architectural extensions provide the base for much larger zSeries machines. This IBM Redbooks publication provides an overview of these changes, and goes into more detail in selected areas. By removing memory, processor, and channel constraints, z990 can be used for major server consolidation activities. More granular options for nondisruptive maintenance, growth, and alterations provide better 7 x 24 x 365 operation. In general, no changes are needed for existing applications--allowing immediate growth into z990. Readers are assumed to have a general understanding of existing S/390 and zSeries hardware. Terms, acronyms, abbreviations, and concepts associated with existing systems are used without further introduction.